3a平方;-2ab-b平方; - ( )= -5a + ab - 2b平方.快
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 16:40:14
3a平方;-2ab-b平方;-()=-5a+ab-2b平方.快3a平方;-2ab-b平方;-()=-5a+ab-2b平方.快3a平方;-2ab-b平方;-()=-5a+ab-2b平方.快(3a&sup
3a平方;-2ab-b平方; - ( )= -5a + ab - 2b平方.快
3a平方;-2ab-b平方; - ( )= -5a + ab - 2b平方.快
3a平方;-2ab-b平方; - ( )= -5a + ab - 2b平方.快
(3a²-2ab-b²)-(-5a+ab-2b²)
=3a²-2ab-b²+5a-ab+2b²
=3a²-3ab+b²+5a
所以填3a²-3ab+b²+5a
3a平方;-2ab-b平方; - ( )= -5a + ab - 2b平方.快
a平方b+ab平方分之a平方-b平方除以(2ab分之a平方-b平方-1)
计算(1)(ab-b平方)/a平方-b平方/a+b(2)a-ab/a+b*(a+b)平方 /b平方-1 (3)a-1/a平方-4a+4/a平方-1/a平方-4
(-2a平方)(ab+b平方)-5a(a平方b-ab平方)
(2a的平方+3ab+b的平方)-(a的平方+ab)
(-2分之1ab平方-3a平方b)平方
-a平方b(a立方b平方-3a平方b+b立方)-2ab平方(a4次方b-3a立方-2ab平方)
4(a平方-2ab)-3(ab-b平方)+5(2a平方-3b平方)
(-3ab的平方+2a的平方b)(3ab的平方+2a的平方b)
5(3a平方b-ab平方)-4(-1/2ab平方+1/3a平方b)
2(a的平方b-3ab平方)-3(2a平方b-7ab 平方)
a的平方b-(-3ab平方)+(-4a平方b)-2ab平方=
5ab平方-4{2a平方b-3{ab平方-2(2ab平方+a平方b)}},其中/a+1/+(b-2)=0
x平方+2(a+b)x-(3a平方-10ab+3b平方)因式分解
3ab{(-2ab)平方-3b(ab-a平方b)+ab平方}算出来多少Rt
2(3ab-a平方)-(2a平方-3平方ab+b平方)先化简再求值
ab(a平方b)-b平方(ab-2a)-3ab平方
5ab的平方+(2a的平方b-3ab的平方)-(ab的平方-3a的平方b)